Transcriptomic and physiological responses of Quercus acutissima and Quercus palustris to drought stress and rewatering - Kim, Tae-Lim; Oh, Changyoung; Denison, Michael Immanuel Jesse; Natarajan, Sathishkumar; Lee, Kyungmi; Lim, Hyemin (Frontiers in Plant Science, 2024)
Establishment of oak seedlings, which is an important factor in forest restoration, is affected by drought that hampers the survival, growth, and development of seedlings. Therefore, it is necessary to understand how seedlings respond to and recover from water-shortage stress. We subjected seedlings of two oak species, Quercus acutissima and Quercus palustris, to drought stress for one month and then rewatered them for six days to observe physiological and genetic expression changes. Phenotypically, the growth of Q. acutissima was reduced and severe wilting and recovery failure were observed in Q. palustris after an increase in plant temperature. The two species differed in several physiological parameters during drought stress and recovery. Although the photosynthesisrelated indicators did not change in Q. acutissima, they were decreased in Q. palustris. Moreover, during drought, content of soluble sugars was significantly increased in both species, but it recovered to original levels only in Q. acutissima. Malondialdehyde content increased in both the species during drought, but it did not recover in Q. palustris after rewatering. Among the antioxidant enzymes, only superoxide dismutase activity increased in Q. acutissima during drought, whereas activities of ascorbate peroxidase, catalase, and glutathione reductase increased in Q. palustris. Abscisic acid levels were increased and then maintained in Q. acutissima, but recovered to previous levels after rewatering in Q. palustris. RNA samples from the control, drought, recovery day 1, and recovery day 6 treatment groups were compared using transcriptome analysis. Q. acutissima exhibited 832 and 1076 differentially expressed genes (DEGs) related to drought response and recovery, respectively, whereas Q. palustris exhibited 3947 and 1587 DEGs, respectively under these conditions. Gene ontology enrichment of DEGs revealed "response to water," "apoplast," and "Protein self-association" to be common to both the species. However, in the heatmap analysis of genes related to sucrose and starch synthesis, glycolysis, antioxidants, and hormones, the two species exhibited very different transcriptome responses. Nevertheless, the levels of most DEGs returned to their pre-drought levels after rewatering. These results provide a basic foundation for understanding the physiological and genetic expression responses of oak seedlings to drought stress and recovery.